The first case of breast cancer in thalassemic patient: case report and review of literature. (12th January 2015) - Picardo, E.; Mitidieri, M.; Minniti, E.; Ambroggio, S.; D'Addato, F.; Benedetto, C.; Gregori, G.; Baù, M. G.
Abstract: Thalassemias are genetic disorders characterized by decreased synthesis of one of the globin chains. Beta-thalassemia is caused by impairment in the production of beta-globin chains leaving the excess alpha chains unstable. With better treatment approaches and improvement in chelation therapy, thalassemic patients are living longer. As a consequence, new complications and associations with other conditions including malignancy have emerged. The occurrence of malignancies in thalassemia has rarely been reported, and our review of the literature revealed only few cases. We report the first case of a thalassemic patient developing breast cancer and discuss the possibility of a link between the two disease entities. This case is intended to alert physicians of the possibility of a malignancy in thalassemia patients.